Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Tax Avoidance Dengan Gender Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016) - Aprilian Kusuma Ningrum; Eny Suprapti; Achmad Syaiful Hidayat Anwar (UMSurabaya Publishing, 2018)
ABSTRACT This research is aim to provide empirical evidence of the influence of corporate social responsibility (CSR) to tax avoidance by genderas moderating variavble . The sample is listed manufactures corporation in Indonesia Stock Exchange, according to purposive sampling method which produces 65 companies. Observation period is 2016. Independent variable disclosure of CSR is measured by using Global Reporting Initiative (GRI) 63 indicator. Dependent variable tax avoidance is measured by using effective tax rate (ETR). Gender moderating variable is measured by the proportion of the women in company’s board of commissioners and board of directors. The data in this research is analized by using SPSS with Moderated Regression Analysis (MRA) method.The result of this research shows that CSR disclosure provides the negative effect totax avoidance. Gender (the proportion of women in company councils) has strengthened the effect of CSR disclosure on tax avoidance practice.Keywords : Corporate Social Responsibility (CSR), Gender, Tax AvoidanceCorrespondence to : apriliankusuma@gmail.com, e.suprapti@yahoo.com